A methodological note on the global Multidimensional Poverty Index (MPI) 2024 changes over time results for 86 countries - Alkire, S; Kanagaratnam, U; Suppa, N (Oxford Poverty and Human Development Initiative (OPHI), 2024)
OPHI MPI Methodological Note No. 60 presents the methodology and policies that underlie the harmonised 233 survey datasets used to produce the harmonised level estimates and their changes over time in multidimensional poverty for 86 countries and 863 subnational regions. 40 of the 86 countries have trends for two points in time, while poverty trends in 36 countries are based on three points in time. Six countries (Benin, Eswatini, Nigeria, Philippines, Tanzania, and Thailand) have results for four points in time, three countries (Ghana, Mexico and Peru) for five time periods and Nepal have trends for six time periods. We also estimate how multidimensional poverty changed by four major age categories (0 to 9 years, 10 to 17 years, 18 to 59 years, and over 60 years) and by two age categories covering children aged 0 to 17 years and adults 18 years and older in all countries. Our results also show poverty trends by rural-urban area.